A representação pós-colonialista da imagem feminina afro-americana em Amada, de Toni Morrison - Kuchar, Jessica Luana (2019)
The main objective of this Conclusion Course Paper is to explain about the identity marks present in the Postcolonial representativeness of the American female image in Amada, by Toni Morrison (2007). Memory and resistance are key axes for understanding this rich work and, in order to structure a consistent analysis, the research was anchored by Postcolonial theoreticians, such as Stuart Hall (1997) (2019), Homi Bhabha (1994), and Thomas Bonnici (2005), and also by feminist theories, with the texts of Chimamanda Ngozi Adichie’s (2015) and bell hooks’s (1997). Also, the critical arguments of Sandra Regina Goulart Almeida’s (2013, Vivan Nickel’s (2009), and Wellington Neves Vieira’s (2014) were very important. Thus, it was possible to understand the real condition of the double subordinate black woman before patriarchal regime.